Design of Extended Channel Ge-source TFET for Low Power Applications - Shokry, Fatma; Shaker, Ahmed; Elsaid, Mohamed; Abouelatta, Mohamed (International Journal of Integrated Engineering, 2020)
In this paper, a novel design of a TFET structure using Ge-source and extending a part of the channel into the source is proposed. The DC performance is analyzed by evaluating the ON current, ION/IOFF ratio and subthreshold swing (SS). Moreover, the high-frequency performance is inspected in terms of transconductance (gm) and unit-gain cutoff frequency (fT). All simulations are performed utilizing 2D SILVACO TCAD. It is demonstrated that the ON current and the cut-off frequency can be simultaneously improved by appropriate design of the proposed structure.